BIOPRIMING CENDAWAN DARK SEPTATE ENDOPHYTES (DSE) UNTUK PENINGKATAN VIABILITAS DAN VIGOR BENIH SENGON (Falcataria falcata (L.) Greuter & R. Rankin) - Bestaf Bestareif; Luluk Setyaningsih; Kurniawati Purwaka Putri (Universitas Nusa Bangsa, 2026)
Sengon (Falcataria falcata) is one of the fast-growing forestry species with high economic value and is widely cultivated in Indonesia. However, a major challenge often encountered is the decline in seed viability and vigor during storage. To address this issue, biopriming technology using dark septate endophytes (DSE) fungi was applied as an invigoration method to improve the physiological quality of seeds.This study aimed to determine the effect of biopriming technology using DSE fungi on the viability and vigor of sengon seeds. The experimental design used was a Completely Randomized Design (CRD) with three treatments, namely without DSE (control), DSE isolate CPGS 3, and DSE isolate S-115, each replicated four times. The observed parameters included germination percentage, germination rate, germination speed index, vigor index, uniformity of germination, and seedling growth rate. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT). The results of the study showed that the DSE CPGHS-3 and DSE S-115 treatments had a significant effect (p<0.05) on the parameters of Germination Power (88-89%) and Seed Growth Rate (8-9%/etmal), but no significant effect (p>0.05) on other seed vigor parameters, such as Germination Rate, Germination Rate Index, Vigor Index, and Seed Growth Simultaneity. The DSE CPGHS-3 strain tended to have a positive impact in the form of an increase in almost all vigor parameters, except for Seed Growth Rate which was constant. Meanwhile, DSE S-115 had a varying effect with a decrease in seed vigor on the Vigor Index and Seed Growth Simultaneity parameters compared to the control. The application of DSE as a biopriming agent to improve seed physiology needs to pay attention to the compatibility between the DSE strain and the type of plant seed.